Recombinant protein CP01850 adjuvanted with Iridea cordata or Sacorpletis skottibergii lipid extracts protected mice against infection by Corynebacterium pseudotuberculosis - Barbosa, Tallyson Nogueira; Scholl, Nicole Ramos; Silva, Mara Thais de Oliveira; Strothmann, Adriane Leites; Pegoraro, Henrique Goncalves; Sousa, Fernanda Severo Sabedra; Seixas, Fabiana Kommling; Bezerra, Francisco Silvestre Brilhante; Collares, Tiago Veiras; de Pereira, Claudio Martin Pereira; Mansilla Muñoz, Andres Omar; Borsuk, Sibele (My University, 2025)
Recently, new immunomodulatory compounds have benn sought as effective adjuvants in vaccine development. In this context, the bioactive substances from macroalgae stand out, as they can satisfactorily activate an immune response against infectious diseases, such as caseous lymphadenitis (CLA), caused by Corynebacterium pseudotuberculosis. This study aimed to evaluate the adjuvant activity of Iridea cordata and Sacorpletis skotibergii lipid extracts associated with the protein rCP01850 against infection by C. pseudotuberculosis in a murine model. Five groups of ten BALB/c mice each were inoculated with 0.9% saline (G1), rCP01850 (G2), rCP01850 + saponin (G3), rCP01850 + Iridea cordata (G4), and rCP01850 + Sacorpletis skotibergii (G5). Two doses of vaccine were administered with a 21-day interval between doses. After that, the animals were challenged with 2 x 10(4) UFC of the MIC-6 strain. Experimental groups G4 and G5 presented protection rates of 60 and 70%, respectively. The production levels of total IgG and its IgG1 and IgG2a isotypes were significantly increased in G4 and G5 after the forty-second day of immunization. In addition, the expression of the cytokines IL-4, IL-12, IL-10, and IFN-gamma significantly increased in G4 and G5 when compared to the negative control (G1). In turn, IL-17 and TNF-alpha had significant expression levels in G4 when compared to the other experimental groups (p < 0.05). The results show that subantarctic macroalgae extracts associated with rCP01850 induced substantial levels of humoral and cellular immune response and protected immunized animals against the challenge.
Keywords: recombinant antigens; natural products; vaccine testing; bioactive compounds; immunoprophylaxis